Perwakafan uang dalam perspektif hukum islam - Rahmawati, Ainia Fikri (Maliki Interdisciplinary Journal, 2026)
As times change, waqf does not not only apply to immovable property , but also movable property such as money. This literature study describes the law of cash waqf according to scholars, practices in institution and mosque, and benefits. From the data analyzed using Miles and Huberman's interactive technique, the results of the study show that cash waqf falls within the realm of ijtihad, which is flexible and open to development. Although there are differences of opinion among scholars of various schools of thought regarding its validity, considering the principles of public interest and the objectives of Sharia (maqasid al-syarī’ah), cash waqf is considered to have Sharia legitimacy and great potential in improving the welfare of the people. Thus, monetary waqf can be positioned as a strategic instrument of Islamic economics that requires professional and sustainable management.